Mapping and Displaying Structural Transformations between XML and PDF - Hardy, Matthew R. B.; Brailsford, David F. (ACM Press, 2002)
Documents are often marked up in XML-based tagsets to delineate major structural components such as headings, paragraphs, figure captions and so on, without much regard to their eventual displayed appearance. And yet these same abstract documents, after many transformations and 'typesetting' processes, often emerge in the popular format of Adobe PDF, either for dissemination or archiving.